PENGARUH VARIASI SUDUT DAN JARAK PENEMBAKAN SANDBLASTING PADA PROSES PRETREATMENT TERHADAP KUALITAS PELAPISAN CAT DAN SIFAT KOROSI PADA BAJA KARBON RENDAH - Saputra, Indra Adi; Widodo, Teguh Dwi; Yuliati, Lilis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The purpose of this study was to determine the effect of variations in the angle and distance of sandblasting on paint coating quality and corrosion properties of low carbon steel. The success of a coating is highly dependent on surface roughness, so sandblasting is needed to clean and create a surface roughness profile with the aim that the paint can coat the surface perfectly. The test method used in this research is the pull off test method for testing the adhesive strength of paint and open circuit potential (OCP) for testing the corrosion potential. The sandblasting variations used are angles of 45⁰, 60⁰, 75⁰ and nozzle distances of 15 cm, 35 and 50 cm. The tests carried out were roughness, paint thickness, paint adhesive strength and corrosion potential. From the test results it can be concluded that the greater the angle and the closer the sandblasting nozzle distance, the greater the surface roughness. The greater surface roughness affects the paint layer to be thicker and has a high paint adhesion strength, resulting in a smaller corrosion potential. In this study, the highest test results were obtained at an angle of 75⁰ and a distance of 15 cm with a surface roughness value of 5.981 µm, a paint thickness of 115 µm, a paint adhesive strength of 7.28 MPa and an initial corrosion potential position of -0.101 V then a final position of -0.063 V.